The Jurist and the world today - Kaplan, Marcos (1972)
This paper contains reflections on the problems of the Latin American crisis and the role of jurists in the face of it. The author mentions that the crisis evidences problems of a socioeconomic, political and juridical nature and that "the new jurist" must contribute to examine the law in order not to be conceived as a static element. His role is to contribute to revitalize the law and overcome its original and structural limitations; acting as a flexible instrument that responds to economic and social changes. For this reason, the author mentions that it is necessary to identify the fundamental problems of the crisis and to provide political, institutional and legal structures that facilitate and promote the necessary socioeconomic and cultural transformations.